Effects of community radio on political education in Ibadan Metropolis, Oyo State, Nigeria - Wasiu Abiodun Makinde; Mobolaji Oluwaseun Abati (Goodwood Publishing, 2024)
Purpose: This study examines the effects of community radio programs on political education in Ibadan Metropolis, Oyo State, Nigeria. Research methodology: This study adopted a survey research strategy, using a mixed method of quantitative and qualitative data. This was a cross-sectional study in which data were collected at one point in time to examine the effects of community radio programs on political education in Ibadan Metropolis, Oyo State, Nigeria. The study population consisted of students, staff, visitors, and residents of the university and its environment. However, Cochran’s (1977) sampling technique was used to determine a sample size of 384 for questionnaire administration. Data were analyzed through descriptive methods using frequency distributions and percentages, as well as inferential statistics through multiple regression analysis. Result: The results show that the regression coefficient for political news is -0.070 and is statistically significant, political advertising is 0.299 and is statistically significant, and political discussion is 0.199 and is statistically significant. From the analysis, only political news does not have a positive relationship but is significant for political education in Ibadan Metropolis, Oyo State, Nigeria. Contribution: This study has been able to establish the level of relationship between community radio programs and political education in Ibadan Metropolis, Oyo State, and Nigeria. Limitation: The study only covers the Ibadan metropolis due to a lack of funds. Extension to a state, region, or all of Nigeria would have provided a more robust argument.